2018
DOI: 10.5935/abc.20180274
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Prevalence, Treatment and Control in Older Adults in a Brazilian Capital City

Abstract: BackgroundThe diagnosis, treatment and control of arterial hypertension are fundamental for a reduction in cardiovascular outcomes, especially in the elderly. In Brazil, there are few studies that specifically identified these rates in the elderly population.ObjectiveTo verify rates of prevalence, treatment and control of hypertension in elderly people living in the urban area of a Brazilian capital city.MethodsA cross-sectional, population-based, randomized, cluster-based study with 912 non-institutionalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
27

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
1
4
0
27
Order By: Relevance
“…In the present study, the statistically significant associations observed in the multiple model between uncontrolled BP and being male, having low alcohol consumption and being a former smoker have also been found in other studies. The relationship between males and uncontrolled BP shows similar results to those of Sousa et al 25 . On the other hand, other authors found no differences between genders 26 .…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the statistically significant associations observed in the multiple model between uncontrolled BP and being male, having low alcohol consumption and being a former smoker have also been found in other studies. The relationship between males and uncontrolled BP shows similar results to those of Sousa et al 25 . On the other hand, other authors found no differences between genders 26 .…”
Section: Discussionsupporting
confidence: 88%
“…Em relação aà faixas etárias que vem sendo acometidas, o DM está mais presente nos indivíduos com idade entre 40 e 59 anos e a HAS naqueles com 60 anos e mais. Ao se analisar a ocorrência segundo o sexo, as duas morbidades acometeram mais fortemente as mulheres, atribuível ao fato de buscarem mais o serviço de atenção primária à saúde, semelhante ao padrão da população feminina brasileira, criando oportunidade para diagnóstico (9,(13)(14)(15)(16) . Estudo realizado em comunidades indígenas australianas, da mesma forma, identificou maior prevalência de DM em mulheres (17) .…”
Section: Resultsunclassified
“…A alteração no modo de vida indígena exibe relação direta com as condições estruturais e culturais, e vem sendo associada às taxas de adoecimento, sobretudo pelo baixo consumo de alimentos naturais e incorporação, na dieta, de produtos industrializados, ricos em carboidratos e lipídios, com baixo teor nutritivo, a exemplo de massas, biscoitos recheados e refrigerantes em faixas etárias cada vez menores (12)(13)(14)(15)(16) .…”
Section: Resultsunclassified
“…Em relação à idade, outro estudo revelou ele-vada prevalência de idosos com pressão arterial elevada e descontrolada e apenas metade dos indivíduos alcançaram metas de controle pressórico, maior entre mulheres (16) . Pesquisa similar constatou que participantes menos aderentes ao tratamento relataram mais complicações associadas à hipertensão arterial (17) .…”
Section: Discussionunclassified